Obesity and Covid-19 Severity - Hussein A. Abdalrudha Al-Baka; Hadeel Haider Aldujaili (Indian Journal of Forensic Medicine & Toxicology, 2021)
This study was to confirm if there was any association between obesity and COVID-19 severity. To achievethis destination we collected data from three hospitals for a period extended from 1st of December 2020 t0to 28th of February 2021 . The data belong to 183 COVID-19 patients. The patients were 148 men, and 35women. Their ages were 33-67 years . all the patient faced severe suffering and hospitalized for differentperiods ( one – two weeks). 26 men and 13 women were with obesity. Percentage of death was 23.07%among the obese men, and 30.76% in the obese women. On the other hand there were 122 men and 22women without obesity. The percentages of death here were 7.37% and 22.72% respectively.